Use of Tangible and Augmented Reality Models in Engineering Graphics Courses - Chen, Y.; Chi, Hung-Lin; Hung, W.; Kang, S. (American Society of Civil Engineers, 2011)
Abstract: Engineering graphics courses are typically a requirement for engineering students around the world. Besides understanding anddepicting graphic representation of engineering objects, the goal of these courses is to provide students with an understanding of the relationshipbetween three-dimensional (3D) objects and their projections. However, in the classroom, where time is limited, it is very difficult toexplain 3D geometry using only drawings on paper or at the blackboard. The research presented herein aims to develop two teaching aids; atangible model and an augmented reality (AR) model, to help students better understand the relationship between 3D objects and theirprojections. Tangible models refer to the physical objects which are comprised of a set of differently shaped pieces. The tangible modelwe developed includes eight wooden blocks that include all the main geometrical features with respect to their 3D projections. The ARmodels are the virtual models which can superimpose 3D graphics of typical geometries on real-time video and dynamically vary viewperspective in real-time to be seen as real objects. The AR model was developed using the ARToolKitPlus library and includes all thegeometrical features generally taught in engineering graphics courses or technical drawing courses. To verify the effectiveness and applicabilityof the models we developed, we conducted a user test on 35 engineering-major students. The statistical results indicated that thetangible model significantly increased the learning performance of students in their abilities to transfer 3D objects onto two-dimensional (2D)projections. Students also demonstrated higher engagement with the AR model during the learning process. Compared to using the screenbasedorthogonal and pictorial images, the tangible model and augmented reality model were evaluated to be more effective teaching aids forengineering graphics courses.